Genetska osnova odpornosti Staphylococcus aureus proti meticilinu - Kocjan, Boštjan (Medicinski razgledi, 2004)
Methicillin-resistant Staphylococcus aureus (MRSA) was firstreported over 30 years ago. Within a decade, MRSA was established as an important nosocomial pathogen in both the adult and pediatric populations. MRSA has also emerged asa pathogen in adults and children without traditional risk factors for MRSA infection. Recent studies have demonstrated that these strains have novel resistance and virulence genes. This review focuses on the epidemiology of MRSA infections and the genetic background of methicillin resistance. The genetic background of methicillin resistance and the transfer of the resistance genes between staphylococci are discussed. A theory of MRSA evolution and the development of major globally spread MRSA clones are presented. In addition, widely used methods for the diagnostic and typing of MRSA isolates are also summarized.
Keywords: Geni bakterijski; Staphylococcus Aureus; Meticilinska rezistenca; Genetics; Bakterijska tipizacija, tehnike; Methicillin Resistance; Polimerazna, verižna reakcija; Genes, Bacterial; bakterije; bacteria; Polymerase Chain Reaction; Bacterial Typing Techniques; genetika; diagnostika; odpornost